An Architecture for Delivering Graphical Web Applications in Constrained IoT Devices - Duarte, Luiz Fernando Heidrich; Zeferino, Cesar; Teive, Raimundo (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2019)
User-interactions with IoT appliances usually occur via raw interfaces, mobile devices, or desktop computers. Besides, during the handling of some devices, the user may be better served by a rich and contextualized embedded interface. This paper presents a distributed architecture for the delivery of graphical web interfaces in constrained IoT devices with an ultra-thin client approach. A strategy for the development of rich and contextualized interfaces for IoT constrained devices is outlined, envisioning a future with the tactile internet. The proposed architecture employs hardware acceleration, fog computing, virtual IoT devices, screen virtualization, and proxy-based web browsing. To validate the architecture, we have implemented a prototype of a constrained smartwatch with a proxy-based web browser. The experimental results show that the proposed architecture is suitable for devices and networks with constrained resources, allowing the display of web apps graphical representations with the potential to offer soft and low-latency user interactions.